Polyketide synthesis in tobacco plants transformed with a plumbago zeylanica type III hexaketide synthase - Jadhav, Supriya; Phapale, Prasad; Thulasiram, Hirekodathakallu V.; Bhargava, Sujata (Phytochemistry, 2014)
A type III polyketide synthase from Plumbago zeylanica (PzPKS) was cloned and expressed in tobacco plants to study whether the transgenic tobacco plants expressing PzPKS synthesize the pharmacologically important polyketide, plumbagin. High resolution mass spectrometry based metabolite profiling of two transgenic events and wild type tobacco plants was carried out to investigate changes in polyketides, including plumbagin. Ten polyketides, which included six pyrones and four naphthalene derivatives, were identified in PzPKS transgenic plants. While one pyrone, styry1-2-pyranone, was detected in both, wild type and transgenic tobacco plants, three pyrones were expressed only in the leaves of transgenic tobacco plants. The transgenic tobacco plants did not accumulate plumbagin, but showed accumulation of isoshinanolone in the roots, which is postulated to be the reduction product of plumbagin. In addition, leaves of transgenic tobacco plants accumulated 3-methyl-1,8-naphthalenediol, a postulated precursor of plumbagin. The results indicated the requirement of additional Plumbago-specific components in the biosynthetic pathway of this polyketide. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: HR-MS; Metabolite profiling; Napthalene derivatives; Plumbago zeylanica L.; Polyketide synthase; Pyrones; Tobacco transgenics